Epidemiological investigation of traumatic spinal cord injury caused by object strike in China: strategies for workplace safety improvement - Wenjie Zhang; Fangyong Wang; Zezheng Chen; Yang Yu; Tao Liu; Honghui Lei; Haoran Yin; Meiling Cheng (Journal of Rehabilitation Medicine)
Objective: Being struck by an object is a major cause of traumatic spinal cord injury in China. This study aims to investigate epidemiological characteristics of spinal cord injury caused by object strike.